Lack of association between the G+2044A polymorphism of interleukin-13 gene and chronic obstructive pulmonary disease: a meta-analysis - Duan, Lian; Liang, Rui; Wang, Zhendong; Lei, Lei; Jin, Lianhong; Shen, Jingling; Jin, Shoude (Molecular biology reports, 2014)
Numerous studies have investigated association of interleukin-13 (IL-13) G+2044A polymorphism with COPD susceptibility; however, the results were inconsistent and inconclusive. To evaluate the association between the IL-13 G+2044A polymorphism and susceptibility to COPD, a meta-analysis of published case–control studies was performed. Based on PubMed and Chinese database, this research selected studies that examined the association of the IL-13 G+2044A polymorphism with COPD. A genetic model-free approach was used to assess whether the combined data showed this association. Then a subgroup analysis was also performed, with stratifications for race, study design, and sample size. Six studies (total 1,213 COPD patients and 801 control subjects) for the IL-13 G+2044A polymorphism with COPD were included in the meta-analysis (G- vs A-allele: OR 1.12, 95 % CI 0.96–1.32, P = 0.15; genotypes GG+GA vs genotype AA: OR 0.99, 95 % CI 0.49–2.00, P = 0.98; genotype GG vs genotypes GA+AA: OR 1.18, 95 % CI 0.97–1.44, P = 0.09; genotype GA vs genotypes GG+AA: OR 0.85, 95 % CI 0.70–1.04, P = 0.11). This meta-analysis demonstrates that the IL-13 G+2044A polymorphism does not confer susceptibility to COPD. More detailed data about individual and environment, larger sample sizes with unbiased genotyping methods and matched controls in different populations are required.